ANALISIS PENERAPAN SISTEM PENGUKURAN KINERJA MANAJEMEN DI PT DUTA INDONESIA DJAYA BERDASARKAN BALANCED SCORECARD - Hemas Mayrina, Djoko Kristianto & Suharno (Universitas Slamet Riyadi, 2016)
This study aims to evaluate the performance of management seen from a financial and non-financial performance. Using case study with the unit of analysis is the place of tourism. Data collection was done through qualitative and quantitative methods. The results of this study demonstrate the performance of a financial perspective that is measured by of 3 a ratio that is Return On Asset (ROA), Gross Profit Margin and Total Asset Turn Over (TATO), generally show good results. Performance from the perspective of customers shows customer satisfaction index obtained from the dissemination of the questionnaire are at a sufficient category. Internal business process perspective is measured with two indicators, namely innovation and operation, the results obtained from the indicators of innovation that is sufficient and operation process is judged less because the percentage error of the recording of transactions has increased. On the perspective of growth and learning is measured using three indicators, namely training of employees, employee attendance and satisfaction of employees. In general the third indicator shows good results.Keywords: balanced scorecard, performance management.